2015
DOI: 10.1371/journal.pone.0143382
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Birth Preparedness and Complication Readiness Interventions on Birth with a Skilled Attendant: A Systematic Review

Abstract: BackgroundIncreased preparedness for birth and complications is an essential part of antenatal care and has the potential to increase birth with a skilled attendant. We conducted a systematic review of studies to assess the effect of birth preparedness and complication readiness interventions on increasing birth with a skilled attendant.MethodsPubMed, Embase, CINAHL and grey literature were searched for studies from 2000 to 2012 using a broad range of search terms. Studies were included with diverse designs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 49 publications
(63 reference statements)
3
53
1
Order By: Relevance
“…There is a need for continued focus on education and sensitisation campaigns to the community on the importance of early ANC attendance. Educational interventions which target both men and women have been reported to increase health seeking behaviour among pregnant women and improve birth preparedness and complication readiness [36,37]. However, despite their importance, most often, sensitisation campaigns are short-lived and thus they may not initiate enough change to enhance long-term behaviour change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need for continued focus on education and sensitisation campaigns to the community on the importance of early ANC attendance. Educational interventions which target both men and women have been reported to increase health seeking behaviour among pregnant women and improve birth preparedness and complication readiness [36,37]. However, despite their importance, most often, sensitisation campaigns are short-lived and thus they may not initiate enough change to enhance long-term behaviour change.…”
Section: Discussionmentioning
confidence: 99%
“…This is intended to ensure that couples are screened for HIV as part of the Prevention of Mother to Child Transmission (PMTCT) programme. The move is also meant to create an opportunity to provide education on danger signs during pregnancy, and on how to become birth-prepared and complication-ready [36]. Implementation of this policy, however, deters men from attending ANC mainly due to fear of HIV screening.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of anthropometry measures varied considerably, yet data on these will be important to avoid adverse pregnancy outcomes, given that maternal under nutrition and short maternal stature are important risk factors for stillbirths . Birth and emergency preparedness is part of the WHO's recommended focused ANC model and demonstrated to be effective for reducing neonatal and maternal mortality through its effect on improving skilled birth attendance and facility deliveries , yet DHS coverage of birth planning interventions was low, and components of birth planning assessed also varied. Birth planning was one of eight interventions with high‐quality evidence supporting its effectiveness in prevention of stillbirths ; therefore, ensuring is implementation as part of ANC packages will be important to monitor.…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic review on the impact of birth preparedness and complication readiness (BPCR) interventions on birth with a skilled attendant revealed that BPCR is a complex intervention, highly dependent on the context in which it is implemented [ 1 ]. We also found that BPCR interventions vary in terms of approaches, actors involved, in definitions applied, in outcomes measured and in the strategies used to evaluate them.…”
Section: Introductionmentioning
confidence: 99%